1997
DOI: 10.1093/oxfordjournals.molbev.a025702
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of extant gymnosperms and seed plant evolution: analysis of nuclear 18S rRNA sequences

Abstract: To study the evolutionary relationships among the four living gymnosperm orders and the interfamilial relationships in each order, a set of 65 nuclear 18S rRNA sequences from ferns, gymnosperms, and angiosperms was analyzed using the neighbor-joining and maximum-parsimony methods. With Selaginella as the outgroup, the analysis strongly indicates that the seed plants form a monophyletic group with the ferns as a sister group. Within the seed plants the angiosperms are clearly a monophyletic group. Although the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
155
1
6

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(182 citation statements)
references
References 54 publications
20
155
1
6
Order By: Relevance
“…The phylogenetic relationships among conifer families obtained in the simultaneous analysis and, in particular, the position of Araucariaceae as sister to Podocarpaceae are in agree- ment with previous phylogenetic hypotheses for the group (Chaw et al 1997;Stefanovic et al 1998;Bowe et al 2000;MagallĂł n and Sanderson 2002;Quinn et al 2002;Rai et al 2008;Leslie et al 2012) and also with the recently proposed classification of Christenhusz et al (2011), in which Araucariaceae and Podocarpaceae belong to the order Araucariales. Today, most of its diversity is restricted to the Southern Hemisphere.…”
Section: Relationships Of Extant Araucariaceaesupporting
confidence: 90%
See 1 more Smart Citation
“…The phylogenetic relationships among conifer families obtained in the simultaneous analysis and, in particular, the position of Araucariaceae as sister to Podocarpaceae are in agree- ment with previous phylogenetic hypotheses for the group (Chaw et al 1997;Stefanovic et al 1998;Bowe et al 2000;MagallĂł n and Sanderson 2002;Quinn et al 2002;Rai et al 2008;Leslie et al 2012) and also with the recently proposed classification of Christenhusz et al (2011), in which Araucariaceae and Podocarpaceae belong to the order Araucariales. Today, most of its diversity is restricted to the Southern Hemisphere.…”
Section: Relationships Of Extant Araucariaceaesupporting
confidence: 90%
“…In this case, as in all the remaining analyses performed, the searches were ended after consensus stabilization. We rooted the trees in the branch leading to Pinaceae because it has been repeatedly obtained as sister of the remaining extant conifer families (Chaw et al 1997;Stefanovic et al 1998;Bowe et al 2000;Quinn et al 2002). mation is also congruent with the combined analysis in terms of relationships within Araucariaceae ( fig.…”
Section: Phylogenetic Analyses Of Extant Araucariaceaementioning
confidence: 53%
“…This analysis also indicated that some manifestation of biochemical functions of very similar di-TPS predated not only the separation of firs and spruces within the pine family, but in fact predated the separation of the Ginkgoales and the Coniferales. Since the Ginkgoales and the Coniferales evolved from a common progymnosperm ancestor (Chaw et al, 1997), this finding suggests that di-TPS of secondary metabolism existed prior to the division of these two orders. In this evolutionary model, we should expect to also find di-TPS of secondary metabolism within other gymnosperm orders, such as the Cycadales.…”
Section: Evolution Of Gymnosperm Tpsmentioning
confidence: 94%
“…Some analyses have placed Gnetales at the base of seed plants (Hamby and Zimmer 1992, Albert et al 1994, Sanderson et al 2000, Rydin et al 2002, but tests using likelihood and other methods suggest that this arrangement is a result of long-branch attraction, particularly affecting third codon positions (Sanderson et al 2000, MagallĂłn and Sanderson 2002, Rydin et al 2002, Burleigh and Mathews 2004. Most analyses, especially those based on combining several genes, have associated Gnetales with conifers, either as their sister group or nested within them, as the sister group of Pinaceae (Goremykin et al 1996, Chaw et al 1997, Hansen et al 1999, Qiu et al 1999, Shindo et al 1999, Winter et al 1999, Bowe et al 2000, Frohlich and Parker 2000, Sanderson et al 2000, Rydin et al 2002, Burleigh and Mathews 2004, Nickerson and Drouin 2004, Kim et al 2004). Trees of this sort offer a more plausible alternative to the anthophyte hypothesis, because many earlier authors pointed out similarities between Gneta-les and conifers, such as linear leaves, elimination of scalariform pitting even in the primary xylem, and compound strobili constructed on a cordaite-like plan (Bailey 1944, 1949, Eames 1952, Bierhorst 1971, Doyle 1978, Carlquist 1996a.…”
Section: Fig 2 Drawings Of Ovulate Structures Of Glossopteridsmentioning
confidence: 99%